Relationship Between Pitcher Fatigue and Medial Elbow Torque in Baseball Pitchers: A Simulated Game Analysis. Issue 7 (30th July 2018) - Makhni, Eric C.; Meldau, Jason E.; Stephens, Jeff; Okoroha, Kelechi; Lizzio, Vincent A.; Meta, Fabien; Ahmad, Christopher S.; Moutzouros, Vasilios
Objectives: The incidence of overuse injury to the elbow in baseball pitchers continues to rise, despite exhaustive efforts at pitch count regulations and emphasis on proper throwing mechanics. The goal of this study was to determine if the medial elbow experiences increased torque levels as the pitcher fatigues through the course of a simulated game. Methods: Competitive baseball pitchers were recruited for this simulated game study. Medial elbow torque was assessed using a validated mobile sensor that recorded medial elbow torque during the throwing motion. A radar gun was used to capture pitch velocity for each recorded pitch. Each pitcher completed a simulated game consisting of 6 innings and a standardized pitching scheme of fastballs, curveballs, and change-ups. Visual analog scores (VAS) measuring fatigue were recorded in between each inning. In total, each pitcher threw 90 pitches. Data was recorded every pitch to include ball velocity, medial elbow torque, arm speed, arm rotation, and arm slot. Results: A total of 11 pitchers (average age 17.6 years; range 15-20 years) completed the study. No adverse outcomes were noted with use of the mobile sensor. VAS scores increased 0.716 points per inning pitched (p<0.001). Medial elbow torque also was found to increase with successive innings, with an increase of 0.836 Nm each inning (p<0.001), while average pitch velocity was found to decrease as the game progressed (0.28 mile per hour decrease per inning; p<0.001). Fastballs generated the highest amount of medial elbow torque. There were no differences found in arm rotation or arm speed as the game progressed. However, the arm slot was found to decrease with each successive inning (0.731 degree decrease per inning; p<0.001). Conclusion: In this simulated game analysis, pitchers were noted to experience increase fatigue after each successive inning. While the average fastball velocity decreased from inning-to-inning, the medial elbow torque was found to increase, signifying a possible risk factor for overuse injury to the medial elbow.